Interdependence of Bitcoin and Other Crypto Money Indicators: CD Vine Copula Approach - Karakas, Ayşe Metin; Demir, Aslıhan Bilici; Çalık, Sinan (My University, 2020)
In recent years, there has been a growing interest on the combination of copulas with mixture model. The combination of vine copulas incorporated into a finite mixture model is also helpful to capture secret structures in a data. This paper aims to examine the relationship between bitcoin and other crypto money indicators with the CD Vine Copula Approach method. In the study, we use closing prices of Bitcoin, Bitcoin Cash, Ethereum, Litecoin, and IOTA. The results show that there is a strong dependence between bitcoin and prominent financial indicators.Keywords: Vine Copula, C Vine copula, D vine copula.
Keywords: İktisat